Sistem Keamanan Sepeda Motor berbasis Arduino Mega 2560 R3 Menggunakan Smartphone Android - Wabdillah, Akbar iskandar (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2020)
The aims of the study were to design and implement a motorcycle safety system based on Arduino Mega 2560 R3 by using Smartphone Android.The data was obtained through 1) Field Research, 2) Library Research. 3) Interview which was conducted at the Makassar City Police (Polrestabes) Makassar. The result of the study indicated that This security system was working based on the input commands from the android smartphone and then was processed through Arduino Mega 2560. The test results of the system designed and based on the results of the questionnaire, obtained 94.7% system eligibility. So this system can be said to be feasible to use.